Hubungan Konsumsi Makanan dan Minuman Manis dengan Risiko Attention Deficit Hyperactivity Disorder (ADHD) - Febrianti, Divani Widya; Pratiwi, Ayu (Jurnal Pustaka Keperawatan (Pusat Akses kajian Keperawatan), 2025)
Mental health is a person's ability to adjust to his or her environment and demonstrate stable and well-behaved personality integration. ADHD is a developmental disorder characterized by an inability to maintain attention, hyperactivity, and impulsive behavior that is not appropriate for the child's developmental stage. The global prevalence of ADHD in children aged 3–12 years is 7.6%. One of the main dietary factors contributing that cause ADHD is sugar and addictive substances.  To determine the relationship between the consumption of sugary foods and drinks and the risk of Attention Deficit Hyperactivity Disorder (ADHD) in students of SD Negeri Periuk 6. Using quantitative methods with correlational descriptive using a cross sectional approach. Sampling technique: This study used startified random sampling. Number of samples: A total of 119 students of SD Negeri Periuk 6. Data analysis: Using the Chi-Square test. The results showed that there was a relationship between the consumption of sugary foods and drinks and the risk of Attention Deficit Hyperactivity Disorder (ADHD) (p-value 0.002). This study shows a relationship between the consumption of sweet foods and beverages and the risk of Attention Deficit Hyperactivity Disorder (ADHD), where higher sugar intake is associated with an increased risk of ADHD. Therefore, regulating the intake of sweet foods and beverages and promoting a balanced diet are important preventive measures from an early age